Pelatihan Akuntansi Berbasis Myob Bagi Koperasi Simpan Pinjam/Unit Simpan Pinjam di Kota Surakarta - Rusdianti, Endang; Wardoyo, Paulus; Purwantini, Sri (Khadimul Ummah, 2019)
The purpose of this service is because the Savings and Loan Cooperative / Savings and Loan Unit is a financial institution that serves funding needs for members and prospective members, must be able to present financial reports accurately and in a timely manner.GenerallyKSP / USP in Surakarta City records transactionsmanually,so that the financial statements consisting of Balance Sheet and Calculation of Operating Results cannot present accurately and on time. This has an impact on decision making and the function of financial management cannot run properly. One solution implemented is to use a Myob-based accounting program, so that the cooperative can present financial reports quickly and accurately. As for the training material, participants are taught the basics of accounting, financial accounting standards, how to install Accounting Myob software version 18, and create an account that is in accordance with the accounts in each KSP / USM, how to fill in the balance / initial balance along with how to operate it , and hands-on practice. The results after participating in this direct training are being able to apply it in the cooperative of each participant.